The Effect of Current Ratio, Total Asset Turnover, and Debt to Asset Ratio on Return on Assets in Food and Beverage Companies Listed in Indonesia in 2019-2021 - Siti Nur Nislakh Febriyanti; Wahyudiono (Journal of World Conference (JWC), 2023)
This study aims to test and prove the Current Ratio, Total Asset Turnover, and Debt to Asset Ratio to Return on Asset. This type of research uses a quantitative approach to secondary data. The population in this study is Food and Beverage companies listed on the Indonesia Stock Exchange in 2019-2021 as many as 30 companies. The sampling method uses documentation techniques so as to produce 10 samples of the company. The data analysis techniques used are multiple linear regression analysis, classical assumption testing, and hypothesis testing. The results of this study show that simultaneously Current Ratio, Total Asset Turnover and Debt to Asset Ratio have a significant effect on Return on Assets. While partially Current Ratio has a significant effect on Return on Asset, Total Asset Turnover does not have a significant effect on Return on Asset and Debt to Asset Ratio has a significant effect on Return on Asset.